Enhanced antibiotic resistance as a collateral COVID-19 pandemic effect? - Ruiz, J. (2021)
It explains the usefulness of antimicrobials, the actions they carry out to apply them against the spread of COVID-19 and claim the delay generated by the lack of adequate knowledge of the usefulness of antibiotics in the population.